2006
DOI: 10.1016/j.yexmp.2005.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The CTLA4 + 49A/G and CT60 polymorphisms and chronic inflammatory arthropathies in Northern Ireland

Abstract: Rheumatoid and juvenile idiopathic arthritis (RA, JIA) are chronic inflammatory arthropathies with an autoimmune background. The cytotoxic T-lymphocyte antigen-4 (CTLA-4) protein plays a key role in the down-regulation of T cell activation.We analyzed the CTLA4 +49A/G and CT60 polymorphisms in cohorts of Northern Irish RA and JIA patients and healthy control subjects using restriction fragment length polymorphism methods.The +49 A allele was increased in RA (61.2%; P = 0.02; OR = 1.28; 95% C.I. = 1.04 -1.58) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
1
29
1
Order By: Relevance
“…15 SNPs within the CTLA4 gene, previously associated with T1D and autoimmune thyroid disease 17 have previously been examined in JIA with conflicting results. 22,23 This may reflect true genetic heterogeneity at this locus or may be due to the modest sample sizes used in previous investigations. We found a weak association of the CTLA4 CT60 SNP (rs3087243) with UK JIA cases (Table 1), although this study only had 53% power to detect an effect (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…15 SNPs within the CTLA4 gene, previously associated with T1D and autoimmune thyroid disease 17 have previously been examined in JIA with conflicting results. 22,23 This may reflect true genetic heterogeneity at this locus or may be due to the modest sample sizes used in previous investigations. We found a weak association of the CTLA4 CT60 SNP (rs3087243) with UK JIA cases (Table 1), although this study only had 53% power to detect an effect (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Because CTLA4 polymorphisms have been associated with several immune diseases, CTLA4 seems to be a general susceptibility locus for autoimmunity, most likely through an altered ability to dampen T cell responses. The association between the A49G single-nucleotide polymorphism in CTLA4 and RA has been frequently investigated, but the results have been inconsistent (39). More recently, however, it was suggested that CTLA4 confers risk to only the subset of ACPA-positive RA patients and not to patients with ACPA-negative disease, potentially adding a third genetic risk factor that contributes mainly to ACPApositive disease (40).…”
Section: Risk Factors For Acpa-positive Ramentioning
confidence: 99%
“…It inhibits T cell activation and maintains peripheral tolerance. As T cells play major roles in the pathogenesis of RA, therefore, regulators of T cells may be influenced by disease susceptibility, such as CTLA-4 [4,12,15,[19][20][21]. The CTLA-4 gene is located on chromosome 2q33 and encodes a 223 amino acid protein [22].…”
Section: Introductionmentioning
confidence: 99%